PERAN INTERNASIONAL CONTACT GROUP DALAM MEDIASI KONFLIK ANTARA PEMERINTAH FILIPINA DAN MORO ISLAMIC LIBERATION FRONT TAHUN 2009 – 2012 - Istiqomah, Heny (DIKSHI (DISKUSI ILMIAH KOMUNITAS HUBUNGAN INTERNASIONAL), 2014)
A BSTRACK The Philippines government has had a prolonged conflict with armed groups in Mindanao, Southern Philippines. One of the most influential groups in Mindanao is the MILF which was established in 1984 by Salamat Hasim. Peace process has been done ??since 1996 but always failed and finally succeeded by the signing of the framework of final peace agreement in 2012 between Philippines government and MILF. The successful agreement reached after negotiation involving third party that is the ICG as a mediator, held. ICG was formed in 2009 consists of United Kingdom, Turkey, Japan, Saudi Arabia, Muhammadiyah, Conciliation Resources, Humanitarian Dialogue Centre, and The Asia Foundation. Therefore, this study aims to describe what roles is ICG played in the conflict mediation between the Philippines government and the MILF in 2009 – 2012. The research shows that ICG has involved in facilitative mediation as explorer, reassure, unifier, convener, facilitator, envisioner, enhancer, guarantor, and legitimizer. This study shows that conflict resolution involving mediation group whose members consists of different backgrounds, match with the conflicts based on ethnicity, culture and religion. Keywords: peace process, facilitative mediation